Context-Aware Authentication with Dynamic Credentials using Electricity Consumption Data. (6th July 2021) - Ustundag Soykan, Elif; KaraÇay, Leyli; Bilgin, Zeki; Tomur, Emrah; Akif Ersoy, Mehmet; KarakoÇ, Ferhat; Çomak, Pinar
Abstract: Industrial IoT (IIoT) era is evolving rapidly in parallel to the progress in Industry 4.0, which leads factories to increase the engagement with external parties through different communication infrastructures. This brings a larger attack surface and requires the development of new security solutions suitable for IIoT systems. Authentication is a key enabler to prevent the attacks that come from the interactions with the outside world components. Though there are proposed authentication schemes for IoT or machine-to-machine (M2M) applications, they cannot be readily applied for IIoT since manufacturing machines have different features and requirements than generic IT and IoT devices. In this paper, context information is proposed to be used for enhancing the authentication process in the IIoT, where instantaneous electricity consumption measured by smart meters is the main context information used as a dynamic authentication credential. Besides, in our method, existing smart meter infrastructure is utilized for both exchanging credentials over an industrial network and verification of the credentials by trusted components like Supervisory Control and Data Acquisition (SCADA) or Energy Management System (EMS). The proposed method also allows the use of other context information as authentication credentials such as temperature and humidity collected by sensors in the manufacturing environment.